Cytochrome p450 and innovative nutraceutical products - Francesco Frati; Giulio Torello; Giuseppe Di Cara (Journal of Biological Research, 2024)
Dietary supplements are products that are ingested in addition to the regular diet to provide additional health-promoting nutrients. Dietary supplements are defined and regulated differently in the European Union (EU) and the United States (US). A fundamental aspect, besides the one related to the composition of the various products on the market, is linked to their quality, both from a nutritional and a pharmacological point of view. Concerning the knowledge of the metabolic aspects, the analysis of the interference, as an inductive or an inhibitory effect, of the p450 enzyme on individual preparations of supplements, is crucial. In this study, we present the results of the interference analysis of a new nutraceutical product based on 38% Bergamot Polyphenolic Fraction BPF® (Citrus bergamia Risso et Poit.), Pomegranate (Punica granatum) and Citrus fruits (Citrus aurantium var. dulcis, Citrus maxima Burm. Merr, Citrus paradisi Macfad) extract with cytochrome p450, showing that the product has limited activity on the cytochromes involved in most of human drug metabolism. This nutraceutical product is to be considered safe and potentially useful in the context of multiple treatments, not interfering with the traditional chronic therapies of patients. These findings open the door to modern "pharma-grade" nutraceuticals, expanding the safety and quality profiles of these new products.